Sistem Pendukung Keputusan Pemilihan Teknisi Broadcasting Pada TVRI Medan Menerapkan Metode MABAC - Dede Winta Sipahutar; Mesran Mesran (STMIK Budi Darma, 2021)
A broadcasting technician is a person in charge of preparing, running, and maintaining electronic equipment used to broadcast television shows, controlling audio equipment to adjust the volume level and sound quality during radio and television broadcasts, running the transmitter to broadcast television shows. To get a reliable broadcasting technician cannot be separated from the recruitment of these technicians to television stations. The broadcasting technician recruitment system carried out at Televisi Republik Indonesia (TVRI) Medan is through a selection stage based on the required criteria using the interview process and the availability of the selection participant files. The weakness that is often experienced by users of the recruitment system is that it is difficult for the leadership to give the final decision regarding the selection participants who deserve to be accepted in an efficient time. To assist the leadership of Televisi Republik Indonesia (TVRI) Medan in the decision-making process in selecting a broadcasting technician, a computer-based application is needed in the form of a decision support system that can provide supporting output for the decision-making. A decision support system is a system that has the ability to solve problems with structured and unstructured problem conditions that have a role in helping problem solving and no one knows how decisions should be made. Decision support systems can be used in assisting the decision making of a selection assessment. Decision support systems aim to provide predictions, provide information and direct information users to be able to make decisions more effectively and efficiently.